2021
DOI: 10.1177/22925503211030017
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Breast Reconstruction: A Canadian Perspective

Abstract: Background: The COVID-19 pandemic has led to unprecedented challenges and restrictions in surgical access across Canada, including for breast reconstructive services which are an integral component of comprehensive breast cancer care. We sought to determine how breast reconstructive services are being restricted, and what strategies may be employed to optimize the provision of breast reconstruction through a pan-Canadian evaluation from the providers’ perspective. Methods: This was a cross-sectional survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Several studies performed since have shown the strict institutional restrictions placed on all autologous breast reconstructions, with 47.7% of surgeons reporting performing only alloplastic reconstructions during the pandemic, while 15.9% reported restrictions on all forms of breast reconstruction. 30 , 38 , 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies performed since have shown the strict institutional restrictions placed on all autologous breast reconstructions, with 47.7% of surgeons reporting performing only alloplastic reconstructions during the pandemic, while 15.9% reported restrictions on all forms of breast reconstruction. 30 , 38 , 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…21,22 During the pandemic, as recently as Spring 2021, breast reconstruction services were reduced up to 90% across Canadian institutions, with an average of 50% reduction since its onset in March 2020. 3 Breast reconstruction was restricted and not performed following mastectomy, as it is considered an "elective" component of surgical care. This pan-Canadian halt in reconstructive services has created a novel cohort of patients, deemed the "COVID-delayed," and refers to women disadvantaged by pandemic restrictions with irreversibly compromised or delayed reconstruction.…”
Section: What Are the Consequences Of Omitting Breast Reconstruction ...mentioning
confidence: 99%
“…2 To maintain adequate resources for critically ill patients, provincial governments restricted surgical services according to hospital capacity, resulting in a marked decrease in availability of operative time. 1,3 For breast cancer patients in whom surgery is the mainstay treatment of choice, surgical care has been delayed and/or compromised. 4 Breast reconstruction following tumor ablation is considered an integral and standard component of comprehensive cancer care, offering women facing mastectomy the choice of restoration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations